Modifiable risk factors for poor health outcomes in multiple sclerosis: The urgent need for research to maximise smoking cessation success. (March 2020) - Marck, Claudia H; das Nair, Roshan; Grech, Lisa B; Borland, Ron; Constantinescu, Cris S
Tobacco smoking is a well-established risk factor for multiple sclerosis (MS) onset, progression and poor health outcomes in people with MS. Despite smoking being a modifiable risk factor, no research has been undertaken to understand how, or who is best placed, to assess or understand smoking behaviour in people with MS, or how healthcare professionals can best assist people with MS to quit. People with MS may have unique motivators to continue smoking, or unique barriers to smoking cessation, that are not addressed by existing cessation tools. Research is urgently needed in this area if the aim is to maximise health outcomes for all people with MS.